Construction of Tungsten Halogen, Pulsed LED, and Combined Tungsten Halogen-LED Solar Simulators for Solar Cell I-V Characterization and Electrical Parameters Determination - Anon Namin; Chaya Jivacate; Dhirayut Chenvidhya; Krissanapong Kirtikara; Jutturit Thongpron (International Journal of Photoenergy)
I-V characterization of solar cells is generally done under natural sunlight or solar simulators operating in either a continuous mode or a pulse mode. Simulators are classified on three features of irradiance, namely, spectral match with respect to air mass 1.5, spatial uniformity, and temporal stability. Commercial solar simulators use Xenon lamps and halogen lamps, whereas LED-based solar simulators are being developed. In this work, we build and test seven simulators for solar cell characterization, namely, one tungsten halogen simulator, four monochromatic (red, green, blue, and white) LED simulators, one multicolor LED simulator, and one tungsten halogen-blue LED simulator. The seven simulators provide testing at nonstandard test condition. High irradiance from simulators is obtained by employing elevated supply voltage to tungsten halogen lamps and high pulsing voltages to LEDs. This new approach leads to higher irradiance not previously obtained from tungsten halogen lamps and LEDs. From I-V curves, electrical parameters of solar cell are made and corrected based on methods recommended in the IEC 60891 Standards. Corrected values obtained from non-STC measurements are in good agreement with those obtained from Class AAA solar simulator.